EJERCICIO Nº 4

f ( x) =

senx + cos x cos x

f ' ( x) =

(cos x − sen x) · cos x − ( sen x + cos x)(− sen x) = cos 2 x

NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 4

f ( x) =

senx + cos x cos x

(cos x − sen x) · cos x − ( sen x + cos x)(− sen x) = cos 2 x cos 2 x − sen x · cos x + sen 2 x + sen x · cos x = cos 2 x f ' ( x) =
NO PASES A LA SIGUIENTE HOJA HASTA QUE NO HALLAS ENTENDIDO ÉSTA. INTENTA ACABAR EL EJERCICIO ANTES DE VER LA SOLUCIÓN

EJERCICIO Nº 4

f ( x) =

senx + cos x cos x

(cos x − sen x) · cos x − ( sen x + cos x)(− sen x) = cos 2 x cos 2 x − sen x · cos x + sen 2 x + sen x · cos x = cos 2 x cos 2 x + sen 2 x 1 = cos 2 x cos 2 x f ' ( x) =

SOLUCIÓN:

f ' ( x) =

1 cos 2 x